A Comparative Study on Takaful Governance between Malaysia and Brunei Darussalam - Nafisah Ruhana; Nur Haziyah Abdul Halim; Ledy Mahara Ginting; Sarah Amalina Azizul Rahman (Journal of Applied Islamic Economics and Finance, 2023)
The aim of this study is to compare takaful governance in Malaysia and Brunei since both countries known for their strong support of takaful. This is to highlight the impact of respective governance on the overall takaful industry in each country. Moreover, the objective of this study is to gain a comprehensive understanding of the governance practices of takaful operators in Malaysia and Brunei. The study will examine a number of important governance mechanisms in both countries and draw comparisons between the governance practices of takaful operators in Malaysia and Brunei. This study use qualitative and descriptive research method to examine and identify similarities and differences in takaful governance between Malaysia and Brunei Darussalam. This is to provide better understanding on how corporate governance for takaful operators influence the takaful operations in both countries. This paper will also emphasized on the key mechanisms of takaful governance and highlighting their duties and responsibilities. This study finds that Malaysia's guide to corporate governance for takaful operators is more fully developed due to its longer-established market. However, corporate governance for takaful operators in both countries is largely similar. Some aspects of Brunei's corporate governance were found to mirror Malaysia's practices